PENGARUH INVENTORY INTENSITY, KONEKSI POLITIK, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK - Bunga Pitaloka (2021)
This study aims to investigate the effect of inventory intensity, political connection, and institutional ownership towards tax aggressiveness. Tax aggressiveness as dependent variable is measured by Book Tax Difference (BTD). The sampling technique used in this research is purposive sampling in mining companies listed on the Indonesian Stock Exchange in 2017-2019. The number of samples in this study were 126 data consisting of 42 companies that met the criteria. The hypotheses were tested using multiple regression analysis. The result of this study indicate that political connection board of directors had a negative and significant effect on tax aggressiveness, while inventory intensity, political connection board of commissioners, and institutional ownership have no significant effect on tax aggressiveness.